2017
DOI: 10.26710/jbsee.v3i1.40
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Electricity Service Quality on the Performance of Manufacturing SMEs in Nigeria

Abstract: Purpose: The objective of this paper is to determine the impact of electricity service quality on both financial and non-financial performance of manufacturing Small and Medium Enterprises SMEs in Nigeria. Design/Methodology/Approach: Survey questionnaire was used to collect data from 201 Managers, Chief executive officers and owner managers of SMEs that are members of Manufacturers Association of Nigeria MAN. Simple regression analysis was done with the use of SPSS version 22.0. Findings: The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Majority of these studies linked organizational e-service activities with organizational level construct, i.e. organizational performance (Muhammed et al , 2017). However, the fact that has largely been overlooked by researchers is the achievement of e-loyalty through high quality of e-service and e-trust (Kaya et al , 2019; Zainul, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Majority of these studies linked organizational e-service activities with organizational level construct, i.e. organizational performance (Muhammed et al , 2017). However, the fact that has largely been overlooked by researchers is the achievement of e-loyalty through high quality of e-service and e-trust (Kaya et al , 2019; Zainul, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of electricity service efficiency on the performance of manufacturing SMEs in Nigeria was checked by Abdulrahim, Issa and Ismaila (2017). 201 survey questionnaires were used by participants of the output association MAN, SPSS, as well as basic regression analysis, was performed.…”
Section: Power Supply and Productivitymentioning
confidence: 99%
“…Surprisingly, not many studies on determinants of banks' profitability in Nigeria have considered this phenomenon. Muhammad, Abdulraheem and Yusuf (2017) argued that electricity service is significantly and positively related with financial performance. They found that the quality of electricity service in Nigeria is a major determinant of both financial and non-financial performance in the Small and Medium Enterprises manufacturing sector.…”
Section: Fueling and Maintenance (Power-running) Costsmentioning
confidence: 99%